Estimating Soil Loss by Water Erosion in Three Different Horticultural Management Systems in Southern Uruguay - Hill, Mariana; Clérici, Carlos; Mancassola, Victoria; Sánchez, Gabriela (Agrociencia Uruguay, 2015)
The current major horticultural production systems of southern Uruguay are little sustainable due to water erosion problems, which determines the need for generation of appropriate mitigation technologies. The Universal Soil Loss Equation is a tool to estimate soil loss that has been adapted and validated for field, forest and pastoral farming systems in Uruguay, but not for horticultural systems. Through the revised version RUSLE (Renard et al., 1997) the relations of soil loss, and from these, the C Factor for three different management were estimated. Measurements were made in three horticultural systems (livestock horticultural rotation, horticultural rotation, and conventional horticulture) during 2008 and 2009. The aim of this work is to generate local information to estimate soil loss from water erosion and potential impacts of climate change due to increased average rainfall erosivity in traditional horticultural systems and the systems proposed by EULACIAS project. Soil loss reductions of 30 % were estimated, which meant achieving tolerable levels. We propose the inclusion of pasture in the rotation as a practice that, in addition to reducing soil loss by 60 % compared to traditional systems, allows adaptation and mitigation to climate change due to increased average rainfall erosivity.